Applying systems biology tools to study n‐butanol degradation in Pseudomonas putida KT2440. Issue 8 (15th June 2015) - Vallon, Tobias; Simon, Oliver; Rendgen‐Heugle, Beate; Frana, Sabine; Mückschel, Björn; Broicher, Alexander; Siemann‐Herzberg, Martin; Pfannenstiel, Jens; Hauer, Bernhard; Huber, Achim; Breuer, Michael; Takors, Ralf
Abstract : To smoothen the process of n ‐butanol formation in Pseudomonas putida KT2440, detailed knowledge of the impact of this organic solvent on cell physiology and regulation is of outmost importance. Here, we conducted a detailed systems biology study to elucidate cellular responses at the metabolic, proteomic, and transcriptional level. Pseudomonas putida KT2440 was cultivated in multiple chemostat fermentations using n ‐butanol either as sole carbon source or together with glucose. Pseudomonas putida KT2440 revealed maximum growth rates (μ) of 0.3 h −1 with n ‐butanol as sole carbon source and of 0.4 h −1 using equal C‐molar amounts of glucose and n ‐butanol. While C‐mole specific substrate consumption and biomass/substrate yields appeared equal at these growth conditions, the cellular physiology was found to be substantially different: adenylate energy charge levels of 0.85 were found when n‐ butanol served as sole carbon source (similar to glucose as sole carbon source), but were reduced to 0.4 when n ‐butanol was coconsumed at stable growth conditions. Furthermore, characteristic maintenance parameters changed with increasing n ‐butanol consumption. 13 C flux analysis revealed that central metabolism was split into a glucose‐fueled Entner–Doudoroff/pentose‐phosphate pathway and an n ‐butanol‐fueled tricarboxylic acid cycle when both substrates were coconsumed. With the help of transcriptome and proteome analysis, the degradation pathway of n ‐butanol could be unraveled, thus representing an important basis for rendering P. putida KT2440 from an n ‐butanol consumer to a producer in future metabolic engineering studies.